O-118 Retrospective exposure assessment and mirna in the exhaled breath condensatein monitoring past exposure to asbestos. (14th March 2023) - Cocco, Pierluigi; Matteis, Sara De; Colosio, Claudio; Visonà, Silvia D; Orrù, Sandro; Cusano, Roberto; Cherchi, Roberto
Abstract : Introduction: Currently, the health surveillance of past exposure to asbestos conveys scarce hope of improving life expectancy and quality. To uplift the screening capability, we validated our retrospective exposure assessment techniques and explored the feasibility of using the miRNA profile in the exhaled breath condensate (EBC) as a biomarker. Material and Methods: We first classified lung fibrosis in the chest HRCT scans of 115 workers formerly exposed to asbestos and retrospectively estimated their exposure. We also assessed past exposure to asbestos and its correlation with the fibre count in the autoptic lung of 24 subjects who died from asbestos-related diseases. Finally, we used an NGS platform to detect miRNAs previously linked to lung cancer and pleural mesothelioma in the EBC of six subjects with no history of past exposure to respiratory hazards. Results: The risk of lung fibrosis increased linearly with time-weighted average (TWA, p = 0.0045) and cumulative exposure to asbestos (p = 0.009). An estimated cumulative exposure ≥ 10 fibre/ml-year conveyed an almost 11-fold (95% CI 1.54–75.7) excess risk of lung fibrosis. Cumulative exposure to asbestos correlated well with the fibre count in the autoptic lung (p = <0.0001). There was a good agreement between the miRNA detection rate in the EBC and plasma samples. The Spearman's correlation between EBC and plasma miRNA counts was significant in 5/6 subjects (p = 0.001 – <0.001). The miRNA profile was consistent among the six participants. Conclusions: Retrospective exposure estimates can reliably reflect past exposure to asbestos. Parenchymal lung alterations show up in relation to estimates of past asbestos exposure much lower than previously thought. EBC sampling is a non-invasive, easily repeatable method to monitor the miRNA profile. It might be profitably used to detect early treatable effects even in subjects with low-level exposure to asbestos.